If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -15 + 2x + -14 = x + -11 Reorder the terms: -15 + -14 + 5x + 2x = x + -11 Combine like terms: -15 + -14 = -29 -29 + 5x + 2x = x + -11 Combine like terms: 5x + 2x = 7x -29 + 7x = x + -11 Reorder the terms: -29 + 7x = -11 + x Solving -29 + 7x = -11 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -29 + 7x + -1x = -11 + x + -1x Combine like terms: 7x + -1x = 6x -29 + 6x = -11 + x + -1x Combine like terms: x + -1x = 0 -29 + 6x = -11 + 0 -29 + 6x = -11 Add '29' to each side of the equation. -29 + 29 + 6x = -11 + 29 Combine like terms: -29 + 29 = 0 0 + 6x = -11 + 29 6x = -11 + 29 Combine like terms: -11 + 29 = 18 6x = 18 Divide each side by '6'. x = 3 Simplifying x = 3
| 5x-2x+12=35-4x-9 | | y=-(1+1)(1-3) | | 2g-8=10-4g | | X^2+7-9=0 | | 105*13/35*8/9 | | 5x-3.2=2x+2.8 | | 7x-91=2x-6 | | 32=17+x/2 | | 9x+10=3x+40 | | 48-2x=16x+24 | | F-2=3f+6 | | 5(x+3)+3(x-1)=-9 | | X/4+7=14 | | 21=(5x/6)+(3x/2) | | 2(x-4)+3(x+5)=2x | | 5.3q-1.9-4.6q=-0.3q-1.5 | | 2x-8+3x+18=2x | | 33/25*10/117*27/22 | | -2y+5x=-9 | | 62-9x=7x+18 | | x/3-26 | | 2x-5=57 | | x/2=48 | | x/4+x/3=7/4 | | 2f-7=43 | | x/6=15 | | x/2=46 | | 5c-11=19 | | 4x+14=112-10x | | 4x^2+3x-7=2x-2 | | 9-5p= | | 3b+7=52 |